Retrieving Accurate Precipitable Water Vapor Based on GNSS Multi‐Antenna PPP With an Ocean‐Based Dynamic Experiment. Issue 6 (21st March 2023) - Wei, Juan; Shu, Yuanming; Liu, Yang; Fang, Rongxin; Qiao, Lulu; Ding, Dong; Li, Guangxue; Liu, Jingbin
Abstract: As an attractive technique for measuring water vapor, the Global Navigation Satellite System (GNSS) faces additional challenges in dynamic applications such as in the open sea. We present a new method of retrieving precipitable water vapor (PWV) based on GNSS multi‐antenna precise point positioning (PPP), which uses GNSS data from multiple antennas and incorporates the constraints of known baseline vector and common tropospheric delay. The 4‐day shipborne dynamic experiment along the China coast demonstrates that the baseline vector constraint shortens the convergence time of positioning and atmospheric parameters, and also slightly improves their accuracies. The common tropospheric delay constraint helps to provide compromised, more robust, and sometimes more accurate PWV estimates. An evaluation with radiosonde‐derived PWVs shows that the combination of the two constraints achieves the best accuracy reaching 4.2 mm. This method helps to expand GNSS meteorology to the vast ocean and benefits satellite altimetry and weather forecasting. Plain Language Summary: Water vapor plays an important role in atmospheric processes ranging from global climate change to mesoscale and micro‐scale weather systems. The Global Navigation Satellite System (GNSS) is an attractive technique to measure water vapor, which has been extensively investigated for ground‐based static stations. In dynamic applications such as in the open sea, it is faced with additional challenges which may potentially degrade the performance. This study presents a new method for retrieving precipitable water vapor (PWV) based on GNSS multi‐antenna precise point positioning (PPP). It uses GNSS data from multiple antennas closely spaced and mounted on the same platform, and incorporates additional constraints of known baseline vector and common tropospheric delay. We have conducted a 4‐day shipborne dynamic experiment along the China coast and demonstrated that this method can shorten the convergence time and provide more robust and sometimes more accurate PWVs compared to conventional PPP. An accuracy level of 4.2 mm is achieved with this method for the ocean‐based dynamic experiment. This study helps to expand GNSS meteorology to challenging environments such as in the open sea, which will benefit weather forecasting and nowcasting. Key Points: A new method of retrieving precipitable water vapor (PWV) is presented based on Global Navigation Satellite System (GNSS) multi‐antenna precise point positioning (PPP) This method can shorten the convergence time and provide more robust and more accurate GNSS‐based PWV The improved performance is helpful to expand GNSS meteorology to the vast ocean and benefits satellite altimetry and weather forecasting